(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The unsafe and indiscriminate usage of pesticides in agriculture presents a major hazard to human health and the environment. This study aimed to assess to levels of knowledge, attitude, and practices of vegetable farmers of Iloilo City toward the safe use of pesticides. A total of 125 farmers participated in this study through site interviews and farm observations. The majority of the farmers are well knowledgeable that pesticides were harmful to health (71%) and the environment (67%). However, farmers’ attitude toward pesticide safety and usage is insufficient. Over 81% of the farmers did not follow pesticide instructions on labels, and 62% did not use personal protective equipment such as respirators and protective boots (29%). Regardless of education, farmer respondents were significantly more likely not to use boots (x2 = 165.95, p<0.05) and respirators (x2 =187.33, 0<0.05) during spraying. An alarming result on the application of pesticides not based on the recommended dosage was practiced by 90% of the farmer respondents (x2=78.90, p<0.05) regardless of the number of years engaging in vegetable production. The same is true with the application of pesticide a week or few days before harvesting was almost practiced by the majority of the farmer respondents (x2=56.01,p<0.05). A significant number (81%) of the farmers reported dizziness and fatigue (67%) as symptoms of acute pesticide poisoning. Although farmers’ knowledge of pesticide hazards was high, the reported safety measures were poor. Comprehensive intervention measures to reduce the health and environmental risks of pesticides are needed, including pesticide safety training programs for farmers, stringent enforcement of pesticide laws, and promotion of integrated pest management and non-synthetic methods of pest control.